The relationship between culture, sustainable use of resources, and financial performance - Engelke, Deon H. (Economic and business review, 2024)
Modelling a dataset of 5230 globally listed firms through two statistical approaches reflecting the primary principles of Natural-Resource-Based Theory and Institutional Theory, respectively, this study provides evidence that sustainability initiatives developed by firms are being rewarded in the form of improved Corporate Financial Performance (CFP). Culture has a significant influence on both firm sustainability performance, captured in ESG ratings, and CFP and also interacts with other variables, including industry sector and socio-economic development of a firm’s markets. This study is unique in hypothesising and statistically proving that sustainability is a mechanism that activates the potential of culture to produce CFP. Natural-Resource-Based Theory (NRBT) and Institutional Theory (DiMaggio & Powell, 1983) provide complementary explanations for the relationship between the culture of a firm and its CFP being mediated by sustainability, effectively determining firms’ approach to the use of their resources in a sustainable or unsustainable way. Certain relationships between culture, sustainability performance, and CFP, however, are better explained by Institutional Theory than NRBT.
Keywords: enterprises; finance; podjetje; sustainable development; trajnostni razvoj